Cultural integration of immigrants in Europe - Algan, Yann (2012)
Taking an economic perspective, this edited collection presents a current, comparative picture of the process of cultural integration of immigrants across Europe. It documents the main economic debates on cultural integration, and provides descriptions of the integration process in 7 main European countries.